Dampak Pembelajaran Daring terhadap Perkembangan Peserta Didik Pada Masa Pandemi Covid-19 - Thoriq Alvin Habibi; Noval Torik Avandi; Indra Pratama (Kampus Akademik Publiser, 2025)
The COVID-19 pandemic has had a very significant impact on aspects of life, including student development. This research aims to examine the impact of the COVID-19 pandemic on students' development in education. The research method used is literature study from various relevant sources. The research results show that this pandemic has caused very significant changes in the learning process, with a shift from face-to-face learning to bold learning. This change brings its own challenges, for example limited access to technology, decreased motivation to learn, and limited social interaction between students and educators. Apart from that, the pandemic also affects the psychological aspects of students, such as increasing stress and anxiety levels. However, there are also some positive innovations and adaptations emerging, such as the use of technology for learning, improved digital skills, and greater awareness of the importance of mental health. This research emphasizes the important role of parents, educators and the government in supporting student development during the pandemic, as well as the need for sustainable strategies to face similar challenges in the future.